2019
DOI: 10.1021/acscatal.9b00787
|View full text |Cite
|
Sign up to set email alerts
|

Merging Catalysis in Single Electron Steps with Photoredox Catalysis—Efficient and Sustainable Radical Chemistry

Abstract: We describe a combination of catalysts that allows the coupling of titanocene­(III) catalysis with photoredox catalysis. Oxidation of radical intermediates by a photoredox catalyst opens novel catalytic mechanisms for reductive epoxide ring opening and redox-neutral epoxide radical arylation. In the former case, the requirement of metallic reductants and stoichiometric acidic additives is bypassed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 44 publications
0
46
0
Order By: Relevance
“…[66] On the other hand, the suitability of the merger of photoredox and Ti IV/III catalysis was recently demonstrated by the group of Gansäuer in a pertinent work. [67] By irradiating with visible light solutions containing a polypyridyl complex (either Ir III or Ru II ) as a photocatalyst (PC), Cp 2 Ti IV Cl 2 and an epoxide, the authors demonstrated the reductive ring opening of the latter to the corresponding alcohol via a radical mechanism supported by the Ti metal center. The mechanism relies on the presence of a sacrificial hydrogen-atom donor (Hantzsch ester, HE; E ox ≈ 0.89 V vs. SCE in DMF [68] ) able to donate a hydrogen atom to the C-centered radical generated upon the SET from the Ti III species coordinate to the epoxide (Scheme 8).…”
Section: Titanocenes In Metallaphotoredox Catalytic Reactionsmentioning
confidence: 99%
“…[66] On the other hand, the suitability of the merger of photoredox and Ti IV/III catalysis was recently demonstrated by the group of Gansäuer in a pertinent work. [67] By irradiating with visible light solutions containing a polypyridyl complex (either Ir III or Ru II ) as a photocatalyst (PC), Cp 2 Ti IV Cl 2 and an epoxide, the authors demonstrated the reductive ring opening of the latter to the corresponding alcohol via a radical mechanism supported by the Ti metal center. The mechanism relies on the presence of a sacrificial hydrogen-atom donor (Hantzsch ester, HE; E ox ≈ 0.89 V vs. SCE in DMF [68] ) able to donate a hydrogen atom to the C-centered radical generated upon the SET from the Ti III species coordinate to the epoxide (Scheme 8).…”
Section: Titanocenes In Metallaphotoredox Catalytic Reactionsmentioning
confidence: 99%
“…[24] Recently, a novel photogeneration of Cp 2 Ti III Cl with the aid of a photocatalyst was reported by the Gansäuer group and Shi group (Scheme 1, b). [25,26] This approach is highly attractive because such an environmentally benign process uses organic electron donors instead of super-stoichiometric metallic reductants. However, it can be surprising at first glance because Cp 2 TiCl 2 is well-known for its intrinsic instability under visible light and decomposes with losing a cyclopentadienyl ligand.…”
Section: Introductionmentioning
confidence: 99%
“…“Metal radical catalysis” [21,22,23,24] or “catalysis in single electron steps” [25] is a concept that combines the advantages of radical chemistry with the privilege of transition metal catalysis and photochemically or electrochemically induced reactions. Implementation of this concept critically depends on the generation of radicals and their conversion to the closed-shell products via reductive elimination or oxidative addition in single electron steps [26].…”
Section: Introductionmentioning
confidence: 99%